Midwifery E-Learning as a Medium for Improving Midwifery Students' Competence in the Digital Era - Al-bahra Al-Bahra; Hardjito S. Darmojo; Ewin Suciana (Unit Penelitian dan Pengabdian Masyarakat STIKES Fatmawati Jakarta, 2026)
The development of digital technology has driven a transformation in the learning system in midwifery education, one of which is through the implementation of e-learning. This study aims to analyze the effectiveness of e-learning as a medium for improving the competency of midwifery students in the digital era. The study employed a mixed methods approach with a sequential explanatory design that combines quantitative and qualitative methods. The quantitative design employed a quasi-experimental pretest-posttest control group design, involving 80 midwifery students divided into e-learning and conventional learning groups. Data were collected through competency tests, questionnaires, observations, and in-depth interviews. Quantitative data analysis was conducted using paired t-tests, independent t-tests, and effect size tests, while qualitative data were analyzed thematically. The results showed that the e-learning group experienced a higher increase in learning outcomes than the conventional group, with a significant difference (p<0.05). The effect size value indicates a significant impact on improving student competency. Furthermore, e-learning also increased students' learning motivation, active participation, learning independence, and digital literacy. Students expressed positive perceptions of the flexibility, ease of access, and interactivity of digital-based learning. However, the implementation of e-learning still faces obstacles such as limited internet connections, technological readiness, and limited direct clinical practice. This study concludes that e-learning is an effective and innovative learning medium for improving the competencies of midwifery students in the digital era, especially when combined with a blended learning approach.